UMPSA and Aschaffenburg University of Applied Sciences strengthen ties to boost Technical Education and WBL Initiatives - Nur Ezzati, Mohd Nasir (UMPSA, 2024)
ASCHAFFENBURG, GERMANY, 22 May 2024 - The Malaysia Technical University Network (MTUN) Advanced TVET delegation, accompanied by the Ministry of Higher Education, continued their first-day work visit to Aschaffenburg University of Applied Sciences (UAS).